TAX AVOIDANCE, CORPORATE GOVERNANCE, KARAKTER MANAJEMEN, DAN KARAKTERISTIK PERUSAHAAN - Nurul Yunita; Yetty Murni; Rafrini Amyulianthy (Jurnal Akuntansi, 2018)
The purpose of this study is to determine the effect of tax avoidance, corporate governance, executive’s character, and firm characteristics. Secondary data for this study were collected from companies included in the category of 100 compasses listed on the Indonesia Stock Exchange in the period 2015. The sample used in this study as many as 54 companies. Based on the results and the conclusion of the research indicate: institutional ownership, independent commissioner, audit quality, executive’s character and leverage do influence tax avoidance. Meanwhile, audit committee and firm size does not affect tax avoidance. Keywords: corporate governance, executive’s character, corporate characteristics, tax avoidance